Forest incomes after Uganda's forest sector reform: Are the rural poor gaining? - Jagger, Pamela (International Food Policy Research Institute, 2008)
Forest sector governance reform is frequently promoted as a policy tool for achieving favorable livelihood outcomes in the low income tropics. However, there is a dearth of empirical evidence to support this claim, particularly at the household level. Drawing on the case of a major forest sector governance reform implemented in Uganda in 2003, this study seeks to fill that gap. The research employs a quasi-experimental research design utilizing pre and post reform income portfolio data for a large sample of households surrounding three major forests in western Uganda; a control group is included in the design. On private forest land overseen by the decentralized District Forestry Service there has been no significant change in average annual household income from forests, and the share of total income from forests has only slightly increased. For households living adjacent to Budongo Central Forest Reserve, overseen by the parastatal National Forestry Authority, there have been significant gains in average annual household income from forests, as well as the share of total income from forests. However, increases are limited to households in the highest income quartile and are primarily attributed to the sale of illegally harvested timber. The findings from this study challenge the view that governance reforms result in favorable livelihood outcomes for the poorest. Policy makers should carefully consider the incentives facing both forestry officials and local resource users with particular attention to increasing awareness of the value of trees and forests, and facilitating legal opportunities for rural smallholders across all income categories to sustainably engage in forest product harvesting and value addition.